STUDENT WORKSHEETS BASED ON DISCOVERY LEARNING INTEGRATED ENVIRONMENTAL LITERACY ON HYDROCARBON MATERIALS - Nur Anisa, Nela; Erika, Farah; Nurhadi, Mukhamad (Universitas Negeri Surabaya, 2025)
Students’ awareness of environmental sustainability issues, particularly the adverse effects of hydrocarbon compound combustion, remains relatively low. To address this concern, this study aims to evaluate the validity of a discovery learning-based student worksheet (LKPD) integrated with environmental literacy within the hydrocarbon topic. The development of the LKPD employed the ADDIE model, limited to the development phase. Validation was conducted by two subject matter experts, two media experts, and two practitioners. The assessment instrument comprised a 38-item questionnaire covering aspects of content feasibility, presentation feasibility, language feasibility, and graphical feasibility. Validation data were analyzed qualitatively through percentage-based score interpretation. The validation results showed scores of 94.56% from subject matter experts, 95.83% from media experts, and 88.28% from practitioners, all falling into the “very valid” category. The reliability test of the instrument yielded a score of 85.71%, indicating that the product is considered reliable. Based on these findings, the LKPD is deemed suitable for further testing to assess its effectiveness and practicality in classroom learning. However, this study is limited to the validation stage; therefore, further classroom implementation is required to evaluate its direct impact on student learning outcomes and attitudes toward environmental issues.